Herbaceous layer development during spring does not deplete soil nitrogen in the Portuguese montado - Otieno, D.O. (2010)
Nitrogen (N) content in the soil and in the herbaceous biomass were monitored during spring of 2004-2006 to determine how the herbaceous layer development influences soil N availability in the montado ecosystem of southern Portugal. Highest (246.6 ± 52.7 g m-2) and lowest (123.2 ± 89.5 g m-2) peak biomass occurred in 2006 and 2005 respectively. Total soilNwithin the top 20 cmsoil profile ranged between 0.2 0.1% in February and 0.41 0.2% inMay,while available soil N was lowest (5 ± 2 μg g-1soil) in February but increased three-to-five fold in March and was >17.5 μg g-1 soil at senescence in May. Significant (p < 0.001) increase in total N in the aboveground pool occurred between February and May. There was however, no decay in soil N content. Instead, the herbaceous vegetation enhanced soil N input and N retention in the ecosystem. Most of the herbaceous plants were annuals with large reserves of organic N at senescence, which returned to the soil as detritus. The herbaceous vegetation is a critical component of the montado that contributes to N recharge and cycling within the ecosystem.